La maison aux esprits : configurations spatiales, pluralité religieuse et syncrétismes dans l’espace domestique afro-cubain - Katerina Kerestetzi (Journal de la Société des Américanistes)
This article proposes an examination of the role of spatiality in the construction of Afro-Cuban religious plurality. The question at the heart of its problematic is the following: how can different religions coexist within the same space, and, especially, how can space enable the expression of religious plurality? In Cuba, Catholics, Protestants, and practitioners of Afro-Cuban religions meet everywhere and at all levels of society despite over half a century of communist rule. But what makes the Cuban case particularly interesting is that religious plurality is often found within a single household, which can accommodate as many religions as there are family members. Such homes generally house a wide range of ritual objects belonging to different religious worlds, such as blood-covered Palo Monte pots; statues and icons of Catholic saints; and effigies of Santería’s deities. How is the domestic space transformed into a ritual one? What are the ritual, cosmological, and reflexive logics enabling such a transformation? How is the household arranged and divided? How are the different religious objects displayed in order to respect the needs and conceptions of each of the various, and often contradictory, religious philosophies? Representing more than just things, Afro-Cuban ritual artifacts are seen by practitioners as true incarnations of gods and spirits, imbued with agency, personality, and preferences. Just as there are opportunities for symbiosis, there are also counterproductive layouts requiring considerable ritual inventiveness and clever use of space. This article will reveal an ecology of ritual objects. Moreover, Cuban households of mixed spirituality are centers of intense rituality. By rituality I am referring to private ritual actions performed on a daily basis but also to the collective ceremonies that bring together the whole religious community. The study of the topographical inscription of this rituality within the domestic space highlights the interactions and tensions between different religious practices as well as the necessary and creative micro-adjustments that allow them to coexist within a shared space.